2021
DOI: 10.1007/s00395-021-00842-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of COMBinAtion therapy with remote ischemic conditioning and exenatide on the Myocardial Infarct size: a two-by-two factorial randomized trial (COMBAT-MI)

Abstract: Manuscript-changes in yellowClick here to access/download;Manuscript;MANUSCRIPT COMBAT MI-BRC-DEF_yellow marked.docx Click here to view linked References Acknowledgements: The COMBAT-MI trial was conceived, designed and led by Prof. David Garcia-Dorado and represents the last contribution of his scientific and medical career dedicated entirely to the search for new and effective cardioprotective strategies that can benefit patients with ischemic heart disease. With this article we want to pay a heartfelt tribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 50 publications
0
20
0
Order By: Relevance
“…If GLP-1 is a common mediator of cardio-and neuroprotection induced by RIC, then administration of GLP-1 stable analogues may offer a better therapeutic solution for the treatment of acute myocardial infarction and ischaemic stroke, especially in patients with autonomic dysfunction. Indeed, exenatide (synthetic Ex4) had been shown to reduce the myocardial injury in patients with myocardial infarction [54], although the results of a recent clinical trial studying the individual effects of RIC, exenatide, and their combination (COMBAT-MI trial) showed no effect of these treatments on infarct size [22]. However, as it was highlighted [11] in that study neither the dose given, nor the plasma concentration of exenatide were known to determine the bioavailability of the drug at the time of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…If GLP-1 is a common mediator of cardio-and neuroprotection induced by RIC, then administration of GLP-1 stable analogues may offer a better therapeutic solution for the treatment of acute myocardial infarction and ischaemic stroke, especially in patients with autonomic dysfunction. Indeed, exenatide (synthetic Ex4) had been shown to reduce the myocardial injury in patients with myocardial infarction [54], although the results of a recent clinical trial studying the individual effects of RIC, exenatide, and their combination (COMBAT-MI trial) showed no effect of these treatments on infarct size [22]. However, as it was highlighted [11] in that study neither the dose given, nor the plasma concentration of exenatide were known to determine the bioavailability of the drug at the time of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…A recent clinical trial COMBAT-MI combining remote ischemic conditioning (RIC) and exenatide administration shows that neither RIC nor exenatide, or their combination, were able to reduce IS in STEMI patients when administered as an adjunct to primary percutaneous coronary intervention ( 110 ).…”
Section: Other Therapeutic Peptides To Treat Mirimentioning
confidence: 99%
“…Our present results confirm previous data obtained by our group in the same animal model [14,15], and support the cardioprotective effect of RIC against myocardial infarction. Unfortunately, however, two recently published randomized clinical trials have not been able to find any effect of RIC on clinical outcomes or on infarct size evaluated by cardiac biomarkers or NMR in STEMI patients [31,32]. Different reasons have been proposed to explain the failure of translation of cardioprotective strategies, including presence of comorbidites, such as aging, diabetes, or hypertension, which may alter the efficacy of cardioprotective maneuvers [33], the routine use of different comedications, such as P2Y12 antagonists, which may have protective effects [34], or the lack of uniformity in the method used to quantify infarct size [32].…”
Section: Cardioprotection By Sdh Inhibition and Ricmentioning
confidence: 99%